DESIGN AND EVALUATION OF OPTICS CONCEPTUAL ASSESSMENT INSTRUMENTS AS A SOURCE OF INFORMATION ON PHYSICS LEARNING - Eko Sujarwanto; Suci Prihatiningtyas (Universitas Negeri Medan, 2018)
Optical phenomena are found in the surrounding environment, both in biotic and abiotic components. Conceptual understanding of optics is needed to explain the occurrence of optical phenomena and be able to apply in technology. This research has been carried out to develop an optics conceptual assessment instrument. The instrument was developed based on the design of Standards for Psychological and Educational Testing. The material included in the instrument developed are reflection, refraction, interference and diffraction. Evaluation of instrument is done through expert validation, validity testing, and reliability testing. The evaluation results show that the instrument is suitable to be used to measure the conceptual understanding of optical topics. The instruments developed are expected to support physics learning